The 1‐Megapixel pnCCD detector for the Small Quantum Systems Instrument at the European XFEL: system and operation aspects. (28th January 2021) - Kuster, Markus; Ahmed, Karim; Ballak, Kai-Erik; Danilevski, Cyril; Ekmedžić, Marko; Fernandes, Bruno; Gessler, Patrick; Hartmann, Robert; Hauf, Steffen; Holl, Peter; Meyer, Michael; Montaño, Jacobo; et al.
Abstract : A description of the 1‐Megapixel pnCCD detector design and capabilities, its implementation at EuXFEL's Small Quantum Systems Instrument both mechanically and from the controls side as well as important data correction steps aim to provide useful background for users planning and analyzing experiments at EuXFEL and may serve as a benchmark for comparing and planning future endstations at other FELs. Abstract : The X‐ray free‐electron lasers that became available during the last decade, like the European XFEL (EuXFEL), place high demands on their instrumentation. Especially at low photon energies below 1 keV, detectors with high sensitivity, and consequently low noise and high quantum efficiency, are required to enable facility users to fully exploit the scientific potential of the photon source. A 1‐Megapixel pnCCD detector with a 1024 × 1024 pixel format has been installed and commissioned for imaging applications at the Nano‐Sized Quantum System (NQS) station of the Small Quantum System (SQS) instrument at EuXFEL. The instrument is currently operating in the energy range between 0.5 and 3 keV and the NQS station is designed for investigations of the interaction of intense FEL pulses with clusters, nano‐particles and small bio‐molecules, by combining photo‐ion and photo‐electron spectroscopy with coherent diffraction imaging techniques. The core of the imaging detector is a pn‐type charge coupled device (pnCCD) with a pixel pitch of 75 µm × 75 µm. Depending on the experimental scenario, the pnCCD enables imaging of single photons thanks to its very low electronic noise of 3 e − and high quantum efficiency. Here an overview on the EuXFEL pnCCD detector and the results from the commissioning and first user operation at the SQS experiment in June 2019 are presented. The detailed descriptions of the detector design and capabilities, its implementation at EuXFEL both mechanically and from the controls side as well as important data correction steps aim to provide useful background for users planning and analyzing experiments at EuXFEL and may serve as a benchmark for comparing and planning future endstations at other FELs.